Prediction of the efficacy of dinoprostone slow release vaginal insert (Propess) for cervical ripening: A prospective cohort study. Issue 9 (6th July 2018) - Daykan, Yair; Biron‐Shental, Tal; Navve, Daniella; Miller, Netanella; Bustan, Mor; Sukenik‐Halevy, Rivka
Abstract: Aim: To evaluate factors predictive of the success of dinoprostone slow release vaginal insert for cervical ripening. Methods: A total of 169 women who underwent cervical ripening with dinoprostone slow release vaginal insert were included in the study cohort. The correlation between parameters present before cervical ripening with dinoprostone slow release and its success, as well as complications and adverse outcomes were analyzed. Results: Dinoprostone slow release vaginal insert was successful in achieving vaginal delivery in 148 of 169 (87.6%), while sufficient ripening was achieved in 140 (83%) cases. Factors associated with successful vaginal delivery were multiparity and younger gestational age at delivery. Factors predictive of the success of cervical ripening with dinoprostone slow release vaginal insert were lower body mass index (BMI), higher parity and perceived contractions prior to insertion. Intrauterine growth restriction was associated with a significant risk for dinoprostone insert removal. Neonatal outcomes were similar in cases of successful or failed ripening. Conclusion: The success of cervical ripening with dinoprostone slow release vaginal insert can be predicted by factors that can be recognized at admission.